SMALL BUT MIGHTY: MARKETING STRATEGIES FOR MSMES LAUNDROMATS - Wibisono, Yogi; Wahdiniwaty, Rahma (Proceeding of International Conference on Business, Economics, Social Sciences, and Humanities, 2024)
This research focuses on developing the right marketing strategy for Small and Medium-sized Enterprises (SMEs) Laundromats, using Panda Laundry Cikampek as a case study. The study employs various matrices such as IFE (Internal Factor Evaluation), EFE (External Factor Evaluation), SWOT, and IE (Internal External) to identify the strengths, weaknesses, opportunities, and threats of the business, with the aim of formulating effective marketing strategies. Findings from this research indicate that Panda Laundry Cikampek has strengths such as Quality of Service to Consumer, Work Environment, Free Pick up and Drop off Within 1Km Radius, Owned Business Premises, Business Owners Carry out Direct Supervision, and Large Parking Lot Available. On the other hand, external evaluation factors indicate Potential Laundry Needs, The High Level of Public Consumption, Technological Development is Getting Faster, Availability of Water Sources, and Consumer Lifestyle Changes as opportunities for the business. Based on these results, the research aims to identify appropriate alternative marketing strategies for SMEs Laundromats.